The im-materiality of urban religion towards an ethnography of urban religious aspirations - Burchardt, Marian 1975-; Westendorp, Mariske (2018)
In recent years, scholars from a wide variety of disciplines have engaged in the study of urban religion. Taken together, these studies form a paradigm that intertwines (1) the politics of belonging, (2) regimes of space and territoriality, (3) materiality and sensorial power and (4) visibility. We argue that while scholars have conceptualised these aspects in very nuanced ways, there is a need to address in a more rigorous way immaterial dimensions of urban religion. We encapsulate these immaterial dimensions in the notion of ‘urban religious aspirations', meaning the multiple ideational sources that underpin people's religious investments in urban life. We illustrate the relevance of studying aspirations with an ethnographic example of two Hong Kong Christian women and their involvement in the Umbrella Movement. Exploring their narratives demonstrates the need to take immaterial aspects of religious life into account when researching urban religion, especially in contexts where the distinction between the religious and the secular is less clearly defined.
Keywords: Hong Kong; Hong Kong Christianity; immateriality of religion; urban aspirations; Urban Religion